Paternal depression: an examination of its links with father, child and family functioning in the postnatal period - Ramchandani, P; Psychogiou, L; Vlachos, H; Iles, J; Sethna, V; Netsi, E; Lodder, A (Wiley-Liss, Inc., 2011)
Background: Maternal depression is common and is known to affect both maternal and child health. One of the mechanisms by which maternal depression exerts its effects on child health is through an increased rate of parental disharmony. Fathers also experience depression, but the impact of this on family functioning has been less studied. The aim of this study was to investigate the association between paternal depressive disorder and family and child functioning, in the first 3 months of a child's life. Methods: A controlled study comparing individual and familial outcomes in fathers with (n = 54) and without diagnosed depressive disorder (n = 99). Parental couple functioning and child temperament were assessed by both paternal and maternal report. Results: Depression in fathers is associated with an increased risk of disharmony in partner relationships, reported by both fathers and their partners, controlling for maternal depression. Few differences in infant's reported temperament were found in the early postnatal period. Conclusion: These findings emphasize the importance of considering the potential for men, as well as women, to experience depression in the postnatal period. Paternal symptoms hold the potential to impact upon fathers, their partners, and their children.